INFLUENCE OF SCHOOL ENVIRONMENT ON THE DEVELOPMENT OF LIFE SKILLS IN SECONDARY SCHOOL STUDENTS - Shobha M.; A.T. Shivaramu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The relationship between Life Skills and the School Environment plays a crucial role in shaping secondary school students’ overall development. Understanding how different aspects of the school environment impact students’ life skills can provide valuable insights for enhancing educational practices. This study investigates this relationship to identify how variations in school environments influence students’ life skills. This study explored the relationship between Life Skills and the School Environment among secondary school students in Hassan district, Karnataka. Using a descriptive survey method, data from 108 students across six schools were analyzed employing mean, standard deviation, correlation, and independent ‘t’ tests, with significance set at 0.05 and 0.01 level. Results revealed a significant positive correlation between Life Skills and the School Environment. Students in better school environments demonstrated higher life skills compared to those in moderate and low environments. These findings suggest that enhancing the school environment could be crucial for developing students’ life skills. Educators and policymakers might consider investing in improving school conditions to foster better life skills among students. Future studies could explore specific elements of the school environment that most strongly impact life skills. Expanding the research to include a larger, state-wide sample could provide a more comprehensive understanding of how changes in the school environment over time influence students’ life skills development. Such an approach would offer broader insights into the effectiveness of various environmental factors and their impact on life skills across diverse educational settings.